FAKTOR-FAKTOR YANG MEMPENGARUHI KEPUTUSAN PEMBELIAN KOPI KOPITALISME DI MASA PANDEMI - Yoga Dian Pratama; Bima Dwi Yunanda; Nenden Sulaehasari (Jurnal Revenue : Jurnal Ilmiah Akuntansi, 2022)
The development of the beverage industry era, many types of beverage products are offered to consumers, one type of beverage product that is generally known and has become a lifestyle today is coffee. Kopitalism adopts the concept of selling 100% pure unmixed ground coffee packaged using a standing pouch at an affordable price but does not reduce the distinctive taste and aroma of robusta coffee in Indonesia. This study aims to determine the factors that influence the decision to buy coffee. The type of research used is an explanatory survey with an associative/relationship study paradigm with quantitative data analysis. Data was collected using a questionnaire, with a sampling technique that is simple random sampling with 35 respondents. The results of the study show that either partially or simultaneously, the three variables, namely price, promotion and quality, have a significant influence on purchasing decisions